Cyclic Nucleotide (cAMP and cGMP) Assays and Capture ELISA for Quantitative Analysis of Plasmodium falciparum Blood-stage Egress - Hackett, Fiona (Bio Protoc, 2014)
Upon rupture of Plasmodium falciparum (P. falciparum) schizonts in vitro (an event known as egress), merozoites are released into the culture medium. The merozoites invade fresh red blood cells, a process that involves shedding of a microneme protein called apical membrane antigen-1 (AMA1) from the merozoite surface. This shedding, which takes place even in the absence of invasion, is therefore a surrogate marker for the degree of egress taking place in a culture, and can be measured using a specific capture ELISA to quantify AMA1 levels in culture supernatants (Collins et al., 2013). The assay uses a monoclonal antibody specific for AMA1 (called 4G2dc1) (Kocken et al., 1998; Collins et al., 2009) to capture and immobilize the protein from culture supernatants, then uses a specific rabbit polyclonal antiserum to detect the immobilized antigen. A phosphatase-conjugated goat anti-rabbit antibody is finally used to quantify the binding of the second antibody. Egress is absolutely dependent upon the activity of a parasite cGMP-dependent protein kinase, PKG, and so is influenced by levels of intracellular cGMP (Collins et al., 2013). This is regulated by the interplay between guanylate cyclases and phosphodiesterases. The latter enzymes may also degrade cAMP, so it may also be informative to measure intracellular cAMP levels.